Keratomalacia and corneal perforation in vitamin A deficiency: Anterior-segment optical-coherence-tomography and histological findings - Julia M. Weller; Theofilos Tourtas; Friedrich E. Kruse (American Journal of Ophthalmology Case Reports)
Purpose: To describe the histological findings and results of anterior-segment optical-coherence-tomography (AS-OCT) in patients with severe keratomalacia and corneal perforation due to vitamin-A deficiency (VAD). Observations: Four patients (3 female, 1 male) with moderate to severe VAD were included in this single-center case series. Keratomalacia/corneal perforation was diagnosed by slit-lamp examination. The findings were documented using photographs and AS-OCT imaging (CASIA-2, Tomey corporation, Nagoya, Japan). Ocular and general medical findings including causes of VAD are reported. VAD was severe (<20 ng/ml) in two patients with chronic alcoholism, and moderate (205/231 ng/ml) in two patients with cachexia. Corneal perforation occurred in 3 out of 4 patients. One patient had severe keratomalacia with impending perforation and massive conjunctival folds with Bitot's spots, which vanished soon after initiation of vitamin A supplementation. In three cases, corneal specimens obtained during anterior lamellar keratoplasty were assessed histologically by light-microcopy. The histological specimens showed massive epithelial thickening and a pronounced granular layer of the corneal epithelium. Conclusions and importance: Keratomalacia leading to corneal perforation is a rare, but possible complication also in countries with sufficient general food supply. The clinico-pathological correlation between AS-OCT and histological findings in patients with VAD is shown in this case series. Typical Bitot's spots were present only in one patient and can be visualized by AS-OCT.